DIDACTIC TRANSPOSITION OF THE SOCCER IN THE CLASSES OF PHYSICAL EDUCATION: EXPERIENCE ON PROJECTS RELATED TO ELEMENTARY SCHOOL (Fiep Bulletin - online, 2014)
It looks for the understanding in the way as the school subjects appropriate of the academic rehearsal of the school Physical Education and of the norms that prescribe it as discipline of the curriculum, for construction of the daily practices. It is noticed with Certeau (1994) that in spite of a power that manufactures rules, norms and values existing, as well as different academic approaches that they glimpse the school Physical Education, countless ways of doing are used for the teachers and students in the teaching institutions. Therefore, for besides the instituted formattings, it is necessary to build a pedagogic practice with the school subjects, considering the contexts and spaces where interfere. It shares an experience with the didactic transposition of the soccer, in times of World Cup, lived starting from problems of the daily practice. In a relationship of shared authority (OLIVEIRA, 2004), search to present a concrete possibility of action practice-theoretical-practice.
Keywords: Physical Education; Daily; Soccer